Paid and Unpaid Overtime Working in Germany and the UK - Olaf Hübler; Robert A. Hart; David N.F. Bell; Wolfgang Schwerdt (Institute for the Study of Labor (IZA), 2000)
Significant numbers of employees work more hours in the workplace than their contract stipulates. Such overtime work can either be paid or unpaid. This research considers overtime working in Germany and the UK and shows that the quantitative significance of both paid and unpaid overtime is greater in the UK. Empirical work is based on the UK Labour Force Survey and the German Socio-Economic Panel in 1993. Overtime influences the effective average hourly wage positively in the case where overtime is paid at premium rates and negatively where such hours are not remunerated. We demonstrate via Mincer wage growth equations that accounting for unpaid work leads to revised estimates of experience and tenure both within and between the two countries. We estimate overtime hours equations, using these to test several of our theories that might explain the apparent irrationality of unpaid work.
Keywords: J22; J23; J33; 330; Unpaid Overtime; hours determination; earnings effects; Überstunden; Lohn; Arbeitszeitflexibilisierung; Betriebszugehörigkeit; Bildungsertrag; Geschlecht; Schätzung; Großbritannien; Deutschland